Methods for screening ginger (Zingiber officinale Rosc.) for bacterial wilt resistance - KUMAR, A. (Indian Phytopathology, 2006)
Currently the bacterial wilt management depends on selection of disease free seed rhizomes, rhizome treatment by hot air or hot water or rhizome solarization, periodical roguing of infected plants and crop rotation with non-host plants to reduce the disease causing potential of soil. Though effective in disinfecting the ginger rhizomes from Ralstonia solanacearum, none of these strategies practically arrested the spread of disease in the field during peak monsoon season, which is highly congenial for horizontal disease spread across the region. Exploitation of host resistance for management of bacterial wilt can be one of the important ecofriendly disease control strategies. To locate resistance against bacterial wilt, a reliable screening procedure becomes vital. Three in vivo methods viz., pseudostem inoculation, soil inoculation, rhizome inoculation and a novel in vitro method i.e., direct incorporation of bacterial cells in the medium when the plantlets are 2-3 leaf stage were evaluated by using different concentration of bacterial cells. Among the different methods evaluated, pseudostem inoculation resulted in wilting of plants in 5-7 days, followed by the soil inoculation method in 7-10 days, rhizome inoculation method in 45-60 days and the in vitro method in 10-14 days. Interestingly, the in vitro method did not result in typical wilting of plants, where the inoculated plants showed only yellowing. One of the observations during the standardization was the occurrence of ‘disease escapes’ among the inoculated plants during the first round of screening, which succumb to disease upon repeated inoculation of pathogen. The PCR assay confirmed the absence of the pathogen in the soil around the uninfected plants, which necessitated the need for three rounds of inoculation for reliable screening for bacterial wilt resistance. Since the soil inoculation closely mimics the natural condition where disease occurs, it is recommended from this study for screening ginger for bacterial wilt resistance. Any surviving plants after three rounds of selection can be further validated through the in vitro method standardized in this work.